Strategi Edukasi Cagar Budaya Kota Banjarmasin Melalui Digitalisasi Berbasis Flipbook - Rahmawati, Maulida; Subroto, Wisnu; Mardiani, Fitri (Universitas Galuh, 2025)
The low awareness of Generation Z towards cultural heritage poses a potential threat to its preservation and utilization in the future. The lack of education about the values and history of cultural heritage is one of the main factors contributing to the youth's lack of awareness about the importance of cultural preservation. Banjarmasin, as a city with rich cultural heritage, requires innovation in the dissemination of cultural information and education to remain relevant to the younger generation. This study aims to develop the digitalization of cultural heritage based on flipbooks as an effort to provide easier access to information about Banjarmasin's cultural heritage. The research method used is a qualitative approach with descriptive analysis through observation, literature review, and interviews with relevant stakeholders, including the community, academics, and policymakers. The results of the study show that flipbook-based digitalization can be an effective strategy in raising awareness and understanding among Generation Z about cultural heritage. Digital flipbooks allow for the presentation of information in a more interactive, engaging, and easily accessible manner, which can increase Generation Z's interest in understanding and preserving local culture. Furthermore, digitalization also contributes to the preservation of cultural heritage by documenting historical information more systematically and sustainably. This research contributes to the development of digital-based education strategies for cultural preservation and opens up opportunities for further innovation in the use of digital technology in education and culture. Thus, the digitalization of cultural heritage through flipbooks not only serves as an educational medium but also as a concrete effort to maintain the continuity of cultural heritage in the digital era.